PEREMPUAN VISIONER ASAL JAWA DALAM CERITA “ASAL USUL KATA MADURA” - Amir Mahmud (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
The main character in the story of Bendoro Gung, King Sang Hyang Tunggal’s daughter, the ruler of Medang Kamulan Kingdom, Java, was told to be the first woman to live in Madura. The purpose of this research is to describe Bendoro Gung's visionary way of thinking while ruling in the plains of Mount Geger. From those values, we can strengthen work ethic and develop community productivity. The theory used in this research is feminism and the research method is descriptive qualitative. The results showed that Bendoro Gung was able to build a better and stronger personality. In fact, she was able to be independent even after receiving punishment from her father. She was able to implement education and religion as the basis for character building, develop a unity between Madurese and Javanese ethnic and equal the role of women in family and society. The values of Bendoro Gung’s ethic, based on the myth of Mount Geger, inspired the community and they decided to develop it as a tourism industry to grow the economy in Madura and also to introduce what kinds of function the folklore have.